Persepsi Orang Tua Siswa tentang Kegiatan Belajar di Rumah sebagai Dampak Penyebaran Covid 19 - Sabiq, Ahmad Fikri (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2020)
The spread of the corona or covid 19 virus has a large impact on various sectors of life. This includes education where students study at home for a long time with the assistance of parents. This study aims to explore and express perceptions of parents in the process of accompanying their children at home. This research method is using qualitative methods. To obtain data, researchers used a questionnaire filled in by a sample of students' parents through stratified random sampling. Data analysis was carried out by means of a descriptive method, namely describing the data after being grouped and analyzing it. From this study the data obtained that the majority of parents feel comfortable with the study program at home. They also hope that this virus will be finished soon so that children can study again at school. Most parents experience difficulties in accompanying their children to study at home. The wisdom of this is that parents can get closer to their families because they have a lot of time staying at home. Another lesson is to be able to practice patience in accompanying learning and knowing and understanding the work of a teacher in school.